Children and Young Adults from the Early Sarmatian Burials of the Lower Volga Region (Paleopathological Perspective) - Evgeniy V. Pererva; Valentina Yu. Chistobaeva (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2018)
This paper presents the results of a study of bone remains of impuberal individuals from the Early Sarmatian burial mounds located in the Lower Volga region. When working with bone remains, we analyzed frequency of occurrence of various stress indicators and other abnormalities, taking into account biological age of the individuals buried there.